2020
DOI: 10.1101/2020.09.08.288308
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regarding theF-word: the effects of dataFilteringon inferred genotype-environment associations

Abstract: Genotype-environment association (GEA) methods have become part of the standard landscape genomics toolkit, yet, we know little about how to filter genotype-by-sequencing data to provide robust inferences for environmental adaptation. In many cases, default filtering thresholds for minor allele frequency and missing data are applied regardless of sample size, having unknown impacts on the results. These effects could be amplified in downstream predictions, including management strategies. Here, we investigate … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 65 publications
1
13
0
Order By: Relevance
“…Interestingly, no overlap in outlier loci between large and small spatial scales was found in a study of the Amazonian forest tree Eperua falcata (Brousseau et al, 2020), suggestive of the presence of multiple adaptation optima occurring through different genetic architectures. Similarly to our study, Brousseau et al (2020) found a substantial number of SNPs in nongenic regions of the genome that were associated with environmental variation, highlighting the ways that experimental designs including multiple spatial scales and annotated reference genomes can increase the potential for identifying false positives (Ahrens et al, 2021). A study of great tits ( Parus major ) in France also found that spatial scale was an important determinant of the significance of urbanisation on genetic differentiation (Perrier et al, 2018), and studies of salmonid fishes have shown that geographically distant populations experience markedly different selection regimes compared to more proximate populations (Fraser et al, 2011), which is likely to give rise to different genomic architectures relating to adaptation.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Interestingly, no overlap in outlier loci between large and small spatial scales was found in a study of the Amazonian forest tree Eperua falcata (Brousseau et al, 2020), suggestive of the presence of multiple adaptation optima occurring through different genetic architectures. Similarly to our study, Brousseau et al (2020) found a substantial number of SNPs in nongenic regions of the genome that were associated with environmental variation, highlighting the ways that experimental designs including multiple spatial scales and annotated reference genomes can increase the potential for identifying false positives (Ahrens et al, 2021). A study of great tits ( Parus major ) in France also found that spatial scale was an important determinant of the significance of urbanisation on genetic differentiation (Perrier et al, 2018), and studies of salmonid fishes have shown that geographically distant populations experience markedly different selection regimes compared to more proximate populations (Fraser et al, 2011), which is likely to give rise to different genomic architectures relating to adaptation.…”
Section: Discussionsupporting
confidence: 83%
“…A total of 51 SNPs were under putative selection at both spatial scales, of which 39 were genic or near‐genic, associated with 28 individual genes. No SNP was identified by both LFMM and RDA at both spatial scales, highlighting the substantially different results that can be obtained depending on the choice of GEA method and spatial scale of sampling (Ahrens et al, 2021). Further, our hypothesis that fundamental differences between spatial scales will result in stronger signals of adaptation in the range‐wide spatial scale was correct.…”
Section: Discussionmentioning
confidence: 95%
“…Table S1 & S2) using the Moran.I function in the package APE (Paradis & Schliep, 2019) to determine the effective sample size (ESS) of each population based on environmental independence. It is worth noting that the eight climatic variables used on both species were not entirely independent, but showed low correlations within one species or the other, though values of r up to 0.7 do not increase the number of false positives detected (Ahrens et al, 2021).…”
Section: Population Differentiation and Genotype-environment Association Analysesmentioning
confidence: 93%
“…Multiple testing can be done using Bonferroni corrections applied to the calibrated p-values. We applied a significance value of (a = 0.001 since lower thresholds were found to be more variable and returned greater numbers of false positives (Ahrens et al, 2021). These thresholds were applied to each of the eight climate variables.…”
Section: Population Differentiation and Genotype-environment Association Analysesmentioning
confidence: 99%
“…Linck & Battey (2019) showed that minor allele frequency (MAF) filtering of datasets may be problematic since it alters the site frequency spectrum (SFS) across loci according to their rate of missingness. Additional recent work has revealed that both variant call rate and MAF can affect population genetic inferences and genotype-environment association studies (Ahrens et al, 2021; Selechnik et al, 2020). In Table 1, we summarise filtering approaches that are commonly applied to RADseq data, the reasons for their usage, and how they can affect population genetic inference.…”
Section: Introductionmentioning
confidence: 99%